Lietuvių muzikos tautiškumo problema. Pietryčių Lietuvos liaudies melodijos XX a. I pusės fonografo įrašuose - Nakienė, Austė (Literatūra, 2015)
In this article, several issues are discussed and related, namely, the phonograph recordings that have recently started being released with Lithuanian folk music from the first half of the 20th century; the folk melodies of the South Eastern Lithuania and the impact from the melodies of the eastern neighbors observed; the formation of professional Lithuanian music, a considerable part of which comprised harmonized folksongs in the beginning of the 20th century. According to the author, the first sound documents were recorded at the turning point, when the centuries-long formation of the Lithuanian folk music dialects was over and the decline of the regional differences started. However, folk music dialects did not vanish without the trace, but were integrated into the professional music culture instead. The change of the Lithuanian music culture in the first half of the 20th century was not a spontaneous process, as the ethnologists and composers began influencing the continuation or break in the traditions. The article is based on the sound recordings, collections of the folk music, the ethno-musicological research, and the written heritage of Eduard Wolter, Aukusti Robert Niemi, Jonas Basanavičius, Mikalojus Konstantinas Čiurlionis, Jonas Balys and Zenonas Slaviūnas.